The importance of slow weight gain in the first 2 months in identifying children who fail to thrive. - Drewett R; Emond A; Blair P; Emmett P (Journal of Reproductive & Infant Psychology, 2005)
A number of authors have suggested that failure to thrive in infancy is best identified by slow weight gain after the child is 6-8 weeks old. The aim of this study was to assess this suggestion by investigating associations between slow weight gain before and after the 6-8 week check and behavioural development at 6 and 18 months. In a whole population cohort based on 12,391 births, infants were identified whose weight gain was in the lowest 5%, taking into account their sex and birthweight. After excluding infants born before or after term or with major congenital abnormalities, the effects of slow weight gain over the period from birth to 9 months was examined using parents' reports concerning items from the Denver Developmental Screening Test at 6 and 18 months. The effects of slow weight gain from birth to 6-8 weeks and from 6-8 weeks to 9 months were then examined separately. Compared with the remainder of the population, the slow gaining infants were significantly delayed at both 6 and 18 months, in analyses that took into account their birthweight and ordinal position in the family, their mother's education, the social class of their family and a number of economic indicators. Relatively delayed development was significantly associated with slow weight gain from birth to 6-8 weeks and from 6-8 weeks to 9 months, but the association with slow weight gain over the earlier period was stronger for both outcome measures. Failure to thrive in infancy is best identified using a weight gain criterion that identifies slow weight gain from birth, rather than one that identifies it by slow weight gain after the child is 6-8 weeks old.